PENGADAAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 17 KOTA JAMBI: pengadaan sarana dan prasarana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Procurement of facilities and infrastructure is one of the important components in supporting the effectiveness and efficiency of educational management in schools. The availability of adequate facilities can improve the quality of the teaching and learning process, while inappropriate management can lead to waste and a decline in the quality of educational services. The purpose of this study is to analyze various research results related to the process of procuring school facilities and infrastructure in realizing efficient educational management. This study was conducted qualitatively with the aim of describing the process of procuring facilities and infrastructure at SMP Negeri 17, Jambi City. The results of this study analyze the transparent procurement process, needs-based planning, and good supervision that contribute significantly to the creation of efficiency in educational management. Thus, schools need to strengthen the planning, implementation, and evaluation systems for procuring facilities and infrastructure so that the goal of efficient educational management can be optimally achieved. Keywords: procurement, facilities and infrastructure.